Pendidikan Berbasis Pesantren: Membentuk Karakter Pribadi Muslim - sudarto, sudarto sudarto (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2018)
Islamic boarding schools are the oldest Islamic educational institutions in the country that contribute greatly to the intellectual life of the ummah and the nation. From the 'womb' of pesantrenlah, community leaders, ulama, intellectuals, and national leaders were born. However, in this era of globalization, pesantren were indeed impressed as 'slum' institutions and not 'popular' choices compared to the many 'modern' schools that emerged. This is what makes the pesantren feel the need to make adjustments in accordance with the National Education System, even though the changes made still cannot change the culture that does exist in the pesantren culture